Genotyping and antibiotic resistance patterns of Campylobacter fetus subsp.venerealis from cattle farms in India. (16th September 2020) - Ishtifaq, A.; Qureshi, S.; Farooq, S.; Kashoo, Z.A.; Malik, Md Z.; Alam, M.R.; Wani, S.A.; Bhat, M.A.; Hussain, M.I.; Dar, R.A.; Shah, S.M.
Abstract: Bovine genital campylobacteriosis caused by Campylobacter fetus subsp. venerealis (Cfv) is of considerable economic importance to the cattle industry worldwide. Cfv causes syndrome of temporary infertility in female cattle, early embryonic mortality, aberrant oestrus cycles, delayed conception, abortions and poor calving rates. In the present study, a total of 200 samples obtained from vaginal swabs, cervicovaginal mucous (CVM), preputial washes and semen straws were investigated that were obtained from organized cattle farm of MLRI, Manasbal and unorganized sectors. Out of a total of 200 samples, 49 (47·57%) vaginal swabs, 1 (3·33%) preputial wash and 8 (25%) carried out CVM samples were positive for Cfv, whereas none of the semen straws were positive for Cfv. A total of eleven isolates of Cfv were recovered. PFGE (Pulse field gel electrophoresis) analysis revealed four different pulsotypes (I–IV) circulating in the screened farms. A common pulsotype circulating among farms could not be established. Insertion element ( ISCfe 1), a 233 bp amplicon of Cfv, was sequenced and the sequence was deposited in GenBank (accession no: MK475662). Abstract : Significance and Impact of the Study: Campylobacter fetus subsp. venerealis (Cfv) is frequently associated with lowered fertility and abortion in ruminants. These infections are responsible for significant reproductive wastage in infected beef and dairy herds and may reduce gross profit margins up to 66%. In India, decreased fertility rates in productive animals are traditionally attributed to brucellosis. However, recently there has been an increase in Brucella ‐negative abortions both in organized and unorganized dairy farms of Kashmir valley, India. Here we investigated the occurrence of bovine genital campylobacteriosis in such farms and assessed the genetic diversity of Cfv isolates. A total of 49 (48%) vaginal swabs, one (3%) preputial washes and 8 (25%) cervicovaginal mucous (CVM) samples were positive for Cfv which in total represent at least four different genotypes.